2019
DOI: 10.1016/j.cub.2019.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Spindle-Length-Dependent HURP Localization Allows Centrosomes to Control Kinetochore-Fiber Plus-End Dynamics

Abstract: Highlights d The HURP protein accumulates on k-fibers inversely proportionally to their length d By setting k-fiber length, centrosomes control HURP accumulation on k-fibers d The relative levels of HURP on k-fibers control plus-end microtubule dynamics d This system allows centrosomes to indirectly control k-fiber plus-end dynamics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 80 publications
5
49
3
Order By: Relevance
“…This is in contrast to somatic cells, as for example reported recently in centrinone-treated RPE1 cells, where centriolar halves are ~50-70% longer than acentrosomal halves (Dudka et al, 2019). The surprising symmetry of acentrosomal and centrosomal spindle halves in the zygote suggests that centrosome-independent pathways play a more important role for spindle assembly and maintenance.…”
Section: Resultsmentioning
confidence: 64%
“…This is in contrast to somatic cells, as for example reported recently in centrinone-treated RPE1 cells, where centriolar halves are ~50-70% longer than acentrosomal halves (Dudka et al, 2019). The surprising symmetry of acentrosomal and centrosomal spindle halves in the zygote suggests that centrosome-independent pathways play a more important role for spindle assembly and maintenance.…”
Section: Resultsmentioning
confidence: 64%
“…DLGAP5/HURP, a K-MT plus-end binding protein gene during mitosis, plays a key role in proliferation and cell cycle progression through spindle assembly [7,[10][11][12]. The previous studies have shown that an increased expression is detected in many cancer types and the tumor cell lines [7,16,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…HURP is highly dynamic, the enrichment in its phosphorylated form at the kinetochore and in its unphosphorylated form at the centrosomes, and tra cking between centrosomes and kinetochores driven by Aurora A-dependent phosphorylation and PP1/PP2A-associated dephosphorylation [11]. Recently, Dudka and his colleagues found that centrosomes also control HURP accumulation on k-bers by setting k-ber length, which it accumulates on k-bers inversely proportionally to half-spindle length [12]. HURP is periodically expressed during the cell cycle and peaks at G2/M, CDK1/cyclin B phosphorylation results in ubiquitination of HURP by SCF and targets it for proteosomal degradation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Centrinone has been used in several studies to investigate the relationship and dependency between the two organelles (Guizzunti and Seemann, 2016;Wu et al, 2016). Moreover, Dudka et al produced human cells which have only one centrosome during mitosis through treatment with centrinone (Dudka et al, 2019). They used these cells as a tool for studying k-fiber dynamics in cells with asymmetric bipolar spindles and found that the centrosome regulated k-fiber plusends in a HURP-dependent manner.…”
Section: Emergence Of Centrinone: a Reversible And Selective Inhibitomentioning
confidence: 99%